Amicarbazone Application Timing Influences Overseeded Perennial Ryegrass (Lolium perenne L.) Safety and Annual Bluegrass (Poa annua L.) Control. Issue 1 (11th January 2014) - Leon, Ramon G.; McCarty, Lambert B.; Estes, Alan G.
Abstract : Amicarbazone controls annual bluegrass ( Poa annua L.) in bermudagrass [ Cynodon dactylon (L.) Pers.] turf overseeded with perennial ryegrass ( Lolium perenne L.). There is, however, a risk of perennial ryegrass injury, depending on application timing. The objective of this research was to determine the effect of the timings between overseeding and amicarbazone applications on perennial ryegrass. Amicarbazone was applied at 0, 2.1, and 2.8 oz a.i./acre at 6, 8, 10, and 12 weeks after overseeding (WAOS) in Florida and South Carolina. In Florida, perennial ryegrass maximum injury was greater at 6 WAOS (79%) than at 8 to 12 WAOS (6 to 30%). Conversely, in South Carolina, minor perennial ryegrass injury was observed in plots treated 6 to 10 WAOS, but 48% injury was observed in plots treated 12 WAOS. In all sites, plots treated at 6 WAOS exhibited up to fourfold reduction in perennial ryegrass cover compared with the untreated control (88%). Overall, annual bluegrass control was acceptable to excellent (73–99%) with amicarbazone applications in South Carolina. In Florida 24 weeks after initial treatment, all treatments controlled annual bluegrass 64 to 98% except applications at 6 WAOS (25–42%). Results suggest that amicarbazone should be applied at least 8 to 10 WAOS to minimize loss of perennial ryegrass cover, but applications at this time will provide adequate annual bluegrass control.